2013
DOI: 10.4049/jimmunol.1203212
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive Th1 Cells Activate Monocytes To Support Regional Th17 Responses in Inflammatory Arthritis

Abstract: We have examined mechanisms underlying the formation of pathologic Th17 cells using a transgenic mouse model in which autoreactive CD4+ T cells recognize influenza virus hemagglutinin (HA) as a ubiquitously expressed self-antigen, and induce inflammatory arthritis. The lymph nodes of arthritic mice contain elevated numbers of inflammatory monocytes (iMO) with an enhanced capacity to promote CD4+ Th17 cell differentiation, and a regional inflammatory response develops in the paw-draining lymph nodes by an IL-17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…As previously reported, the majority of TS1xHACII mice (but not mice expressing either the TS1 or HA transgenes alone) spontaneously develop inflammatory arthritis, as evidenced by overt joint inflammation and swelling that can affect both front and rear paws (Fig. 1B) (2830). Joint inflammation first becomes evident between 6 and 8 wk of age, and by 14 wk almost all TS1xHACII mice have developed at least 1 inflamed paw (Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…As previously reported, the majority of TS1xHACII mice (but not mice expressing either the TS1 or HA transgenes alone) spontaneously develop inflammatory arthritis, as evidenced by overt joint inflammation and swelling that can affect both front and rear paws (Fig. 1B) (2830). Joint inflammation first becomes evident between 6 and 8 wk of age, and by 14 wk almost all TS1xHACII mice have developed at least 1 inflamed paw (Fig.…”
Section: Resultssupporting
confidence: 77%
“…We have addressed these questions using a transgenic mouse model in which autoreactive CD4 + T cells with defined specificity for a surrogate self-peptide drive the spontaneous development of inflammatory arthritis (2830). By varying the reactivity of the CD4 + T cell response to a single self-peptide, we show that B cells are not required for arthritis to develop in the context of a strongly autoreactive CD4 + T cell response (although pro-inflammatory cytokines such as TNF are required).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, IFN␥ has been shown to induce human antigenpresenting cells to generate IL-1 and IL-23, thereby promoting the development of Th17 cells and abating the polarization of Th1 cells (43). Similarly, Simons and colleagues recently demonstrated an IFN␥-dependent accumulation of inflammatory monocytes in the lymph nodes of arthritic mice, which were regionally activated by autoreactive Th1 cells to promote Th17 cell differentiation (44). These findings are consistent with the time course of IFN␥ and IL-17A polarization demonstrated in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This coincided with increasing Th17 cell differentiation suggesting Th17 cells to play a role in this phenomenon. However, a role for IL-12-induced IFNg cannot be fully excluded, as it was recently proposed that IFNg activates monocytes, which in turn drive the production of IL-17-producing T cells [63]. In a proof-of-concept study, an antibody targeting IL-17A was shown to enhance the relief from RA symptoms seen with disease-modifying antirheumatic drugs [64].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%